Patterns of diversification in small New World ground doves are consistent with major geologic events. (31st December 2014) - Sweet, Andrew D.; Johnson, Kevin P.
Abstract: South America has undergone many dramatic changes during the past 60 million years, which has had a major impact on the patterns of biological speciation and diversity in the region. Birds have been particularly affected, and major geologic events have been an important factor in generating avian diversity in the New World. Here we investigate the impact of two geologic events, Andean uplift and the Panamanian land bridge formation, on the speciation and diversification patterns of birds in the New World using a broadly dispersed clade, the small New World ground doves (Aves: Columbidae). Using complete species-level sampling for the clade (barring 2 possibly extinct species), we used sequences of 4 mitochondrial genes and 1 nuclear gene to infer a phylogenetic tree for the group. To address historical biogeographic questions, we estimated divergence times and reconstructed ancestral ranges. The phylogenetic analysis resulted in a well-supported tree. Divergence time estimates and historical biogeographic reconstruction indicated a South American origin for the clade, with several speciation events coinciding with either Andean uplift events or the land bridge formation. These results indicate how major geologic events affected the diversification of this group of birds, and lead to a broader understanding of the impact of these events on patterns of speciation in New World birds.